2014
DOI: 10.1007/s40071-014-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density-dependent growth and survival of Asian red-tailed catfish (Hemibagrus wyckioides) fries: early nursing in cages

Abstract: Asian red-tailed catfish (Hemibagrus wyckioides) were raised at five different stocking densities in cages (submerged and with a volume of 1 m 3 ) suspended in a fish pond from July to August 2012. H. wyckioides fries (mean weight 0.8 ± 0.1 g) were stocked at densities of 25, 50, 100, 200, and 400 fish/m 3 . At the end of 56 days, the mean fish weights among the stocking densities of 25 and 50 fish/m 3 were significantly lower than those of the 100, 200, and 400 fish/m 3 density. The specific growth rates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This means that decreasing the stocking density gave a positive effect (P ≤ 0.05) of final weight gain. These results agreed with many authors (34)(35)(36)(37)(38), where they found that increased stocking density resulted in less AWG, ADG and SGR.…”
Section: Growth Performance and Survival Ratesupporting
confidence: 93%
“…This means that decreasing the stocking density gave a positive effect (P ≤ 0.05) of final weight gain. These results agreed with many authors (34)(35)(36)(37)(38), where they found that increased stocking density resulted in less AWG, ADG and SGR.…”
Section: Growth Performance and Survival Ratesupporting
confidence: 93%
“…Hemibagrus wyckioides is well accepted by consumers in several Southeast Asian countries as food fish due to its excellent taste (Rahmah et al, ; Sahoo, Giri, Chandra, & Sahu, ). In addition, there was no cannibalism in the cage rearing of this species unlike other catfish (Jiwyam & Nithikulworawong, ), which makes it an excellent species for intensive aquaculture (Ng and Rainboth, ). Nowadays, H. wyckioides is popular in cage and pond culture in the Mekong River Basin including Yunnan Province, China.…”
Section: Introductionmentioning
confidence: 96%
“…This species is very popular with farmers and consumers for its fast growth rate, large size, extensive adaptability, and superior resistance to disease [14,15]. In addition, this catfish do not exhibit cannibalism phenomenon unlike other catfish [16]. Although this species is widely cultured in ponds and cages throughout the Lancang-Mekong River Area, there is no special compound feed for H. wyckiodies due to limited information on the requirements of nutrients [13,[17][18][19] and utilization of feed ingredients [20,21].…”
Section: Introductionmentioning
confidence: 99%